2023
DOI: 10.3390/biology12050697
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Intrinsic Therapeutic Targets for Metastatic Breast Cancer

Jiawei Li,
Eyleen L. K. Goh,
Ji He
et al.

Abstract: Breast cancer is now the most common cancer worldwide, and it is also the main cause of cancer-related death in women. Survival rates for female breast cancer have significantly improved due to early diagnosis and better treatment. Nevertheless, for patients with advanced or metastatic breast cancer, the survival rate is still low, reflecting a need for the development of new therapies. Mechanistic insights into metastatic breast cancer have provided excellent opportunities for developing novel therapeutic str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 261 publications
0
4
0
Order By: Relevance
“…The AKT signaling pathway is essential in regulating biological functions such as proliferation, apoptosis and invasion [42] and is known to be hyperactivated in various cancers, making it a pivotal target for cancer therapy [43,44]. Specifically, AKT has been identified as a key therapeutic target for breast cancer, playing a significant role in aerobic glycolysis [45].…”
Section: Discussionmentioning
confidence: 99%
“…The AKT signaling pathway is essential in regulating biological functions such as proliferation, apoptosis and invasion [42] and is known to be hyperactivated in various cancers, making it a pivotal target for cancer therapy [43,44]. Specifically, AKT has been identified as a key therapeutic target for breast cancer, playing a significant role in aerobic glycolysis [45].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, 75% of patients with breast cancer showed the activation of the insulin/IGF-1R signaling pathway. This signal transduction axis is related to the increase in cancer progression, angiogenesis, and metastasis [ 29 ]. The IGF signal axis is implicated in TNBC, and the IGF gene signature is upregulated in TNBC and TNBC cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…TrxR/Trx regulate glyceral dehyde-3-phosphate dehydrogenase (GAPDH) by altering the glycolytic pathway [39]. Moreover, TrxR/Trx activate p53 and hypoxia-inducible factor 1α (HIF-1α), affecting cell proliferation [40], as well as angiogenesis and metastasis [41,42], which may have applications in the development of therapeutic strategies [43][44][45].…”
Section: Biochemical Aspects Of Breast Cancer and Oxidative Stress 21...mentioning
confidence: 99%